2018
DOI: 10.1002/clc.22872
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial volume in patients with HER2‐positive breast cancer: One step further to predict trastuzumab‐related cardiotoxicity

Abstract: BackgroundTrastuzumab (TZ) therapy requires careful monitoring of left ventricular (LV) ejection fraction (LVEF) because it can be potentially cardiotoxic. However, LVEF is an imperfect parameter and there is a need to find other variables to predict cardiac dysfunction early. Left atrium (LA) enlargement has proven to be a powerful predictor of adverse outcomes in several disease entities.HypothesisBaseline LA volume enlargement might predict TZ‐related LV dysfunction.MethodsHER2‐positive breast cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
5
19
0
Order By: Relevance
“… 13 In breast cancer patients receiving chemotherapy, LA dilatation has been proven to be related to the occurrence of cardiac dysfunction. 14 However, in a study conducted among long‐term survivors of childhood cancer treated with anthracyclines, the LAVI of the chemotherapy group decreased notably compared with that of the control group. However, LAEF did not change significantly.…”
Section: Discussionmentioning
confidence: 98%
“… 13 In breast cancer patients receiving chemotherapy, LA dilatation has been proven to be related to the occurrence of cardiac dysfunction. 14 However, in a study conducted among long‐term survivors of childhood cancer treated with anthracyclines, the LAVI of the chemotherapy group decreased notably compared with that of the control group. However, LAEF did not change significantly.…”
Section: Discussionmentioning
confidence: 98%
“…Recently published studies showed significant dilatation and reduction in LA contractile function in patients after chemotherapy [6,7,8]. The authors claimed that LA dilatation during chemotherapy predicted cardiotoxicity development in HER2-positive breast cancer patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently published studies showed significant dilatation and reduction in LA contractile function in patients after chemotherapy [6,7,8]. The authors claimed that LA dilatation during chemotherapy predicted cardiotoxicity development in HER2-positive breast cancer patients [8]. A recent investigation showed that it was not baseline LAV that indexed for BSA (LAVI), but that increment of LAVI during trastuzumab was associated with cardiotoxicity [9].…”
Section: Introductionmentioning
confidence: 99%
“…LA enlargement and dysfunction may relate with higher risk of cardiotoxicity during therapy in breast cancer [ 33 , 34 ]. Furthermore, a retrospective study including 92 therapy-naive cancer patients and their matched controls suggests that LA reservoir and functions are deteriorated in the cancer group [ 35 ].…”
Section: Atrial Cardiomyopathy In Cancermentioning
confidence: 99%